UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER PESERTA DIDIK MELALUI BUDYA RELIGIUS KELAS X DI SMKN 4 MALANG - Fadlila Fadlila; Abdul Jalil; Khoirul Asyfiak (VICRATINA, 2020)
This research was taken through several problems that were found at the time of the study, namely the problem of character building students through the religious culture that exists in the SMKN 4 Malang such as lack of awareness, discipline of students in carrying out fardhu prayer obligations and lack of students' responsibilities towards the tasks given the teacher. Through some of these problems is part of the responsibility of a teacher of Islamic education. This research was conducted using a type of case study research with a qualitative approach. The research technique is through observation, interviews and documentation. The results showed that the PAI teacher's strategy in shaping the character of students, through learning in the classroom and activities outside the classroom. The cultural conditions at SMKN 4 Malang are also quite good, this can be known through a number of activities at school. The results obtained by the PAI teacher from the formation of character through religious culture have begun to be seen with the change in attitudes of students who begin to be disciplined, and responsible.